ANALYSIS OF THE INFLUENCE OF EWOM AND PRODUCT DESIGN ON PURCHASING DECISIONS OF ELECTRIC MOTORCYCLES IN SOLO RAYA - Muhammad Rafly Chairulloh; Moechammad Nasir (ITB AAS Indonesia Surakarta, 2024)
This study aims to analyze the effect of EWOM and Product Design on purchasing decisions for electric motorcycles in Solo Raya. The sample used in this study amounted to 200 respondents who were in Solo Raya. The sampling method using purposive sampling and the data used was primary data in the form of a quetionnaire. The analytical tools used in this study include the measurement model (outer model), Inner model evaluation, and hypothesis testing using the SmartPLS software. The results of this study indicate that the EWOM variable has a positive effect on purchasing decisions and the Product Design variable has a positive effect on purchasing decisions. This means that all variables in EWOM and Product Design have a positive effect on purchasing decisions for electric motorcycles in Solo Raya.